The fact of pure reason: the foundation of the categorical imperative in Kant's critique of practical reason - Moledo, Fernando (2018)
The aim of this paper is to discuss why and how the teory of the factum of pure reason in the critique of practical reason replaces the deduction of the categorical imperative given a few years earlier in the groundwork of the metaphysics of morals. To that purpose I propoose an interpretation as to why Kant rejects the possibility of giving a deduction of the categorical imperative in the critique of practical reason. I focus then on Kant's factum theory and the argue that it does give a justification for the categorical imperative. This justification should be understood, however, as a practical justification because it does not explain the theoretical ground for the validity of the moral law, but relies on the very fact that to act entails awareness of our obligation through moral feeling.